blaNDM and mcr-1 to mcr-5 Gene Distribution Characteristics in Gut Specimens from Different Regions of China - Dongyue Lv; Ran Duan; Rong Fan; Hui Mu; Junrong Liang; Meng Xiao; Zhaokai He; Shuai Qin; Jinchuan Yang; Huaiqi Jing; Zhaoguo Wang; Xin Wang (MDPI AG, 2021)
Antibiotic resistance has become a global public health concern. To determine the distribution characteristics of mcr and blaNDM in China, gene screening was conducted directly from gut specimens sourced from livestock and poultry, poultry environments, human diarrhea patients, and wild animals from 10 regions, between 2010-2020. The positive rate was 5.09% (356/6991) for mcr and 0.41% (29/6991) for blaNDM, as detected in gut specimens from seven regions, throughout 2010 to 2019, but not detected in 2020. The detection rate of mcr showed significant differences among various sources: livestock and poultry (14.81%) > diarrhea patients (1.43%) > wild animals (0.36%). The detection rate of blaNDM was also higher in livestock and poultry (0.88%) than in diarrhea patients (0.17%), and this was undetected in wildlife. This is consistent with the relatively high detection rate of multiple mcr genotypes in livestock and poultry. All instances of coexistence of the mcr-1 and blaNDM genes, as well as coexistence of mcr genotypes within single specimens, and most new mcr subtypes came from livestock, and poultry environments. Our study indicates that the emergence of mcr and blaNDM genes in China is closely related to the selective pressure of carbapenem and polymyxin. The gene-based strategy is proposed to identify more resistance genes of concern, possibly providing guidance for the prevention and control of antimicrobial resistance dissemination.